Using structural equation modeling to explore the influences of physical activity, mental health, well-being, and loneliness on Douyin usage at bedtime - Luo, Hongcheng; Zhang, Xing; Su, Songpeng; Zhang, Mingyang; Yin, Mingyue; Feng, Siyuan; Peng, Rui; Li, Hansen (Frontiers in Public Health, 2024)
Using structural equation modeling to explore the Influences of Physical Activity, Mental Health, Well-being, and Loneliness on Douyin Usage at bedtime